2010
DOI: 10.2152/jmi.57.326
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical features of lung cancer patients from 1999 to 2009 in Tokushima Prefecture of Japan

Abstract: Lung cancer is the leading cause of malignancy-related death worldwide. In the present study, we reviewed the epidemiologic and clinical features of lung cancer in Tokushima Prefecture, Japan. Between January 1999 and December 2009, 2,183 patients with lung cancer were enrolled in this study. One thousand five hundred ninety-one (73%) patients were male and 592 (27%) patients were female. Median age was 70 years, with a range of 15-93 years. Seventy-six percent of patients had smoking history. One thousand nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
0
13
1
Order By: Relevance
“…The male/female ratio in India has been found as 4.1/1, which is lower than the results in our study (Dey et al, 2012). In Japan the ratio is 2.8/1 (Kanematsu et al, 2010). In a study in 2010, 255 patients diagnosed with lung cancer in 2005, 220 of whom (86.3%) were male and 35 were female (13.7%) are evaluated in Erzurum (Araz et al, 2010).…”
contrasting
confidence: 78%
See 2 more Smart Citations
“…The male/female ratio in India has been found as 4.1/1, which is lower than the results in our study (Dey et al, 2012). In Japan the ratio is 2.8/1 (Kanematsu et al, 2010). In a study in 2010, 255 patients diagnosed with lung cancer in 2005, 220 of whom (86.3%) were male and 35 were female (13.7%) are evaluated in Erzurum (Araz et al, 2010).…”
contrasting
confidence: 78%
“…One of the leading cause of cancer-related death worldwide is lung cancer with 1.18 million deaths of the world total (Kanematsu et al, 2010). Recent studies about epidemiology of lung cancer have showed that disease continues to be diagnosed considerably more in men than women (Araz et al, 2010;Kanematsu et al, 2010;Dey et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, lung cancer is the leading cause of cancer-related death in Japanese males and the second leading cause of cancer-related death in Japanese females, respectively 7 . This poor prognosis is mainly due to the unfavorable fact that lung cancer is often diagnosed at an advanced stage 8, 9, 10, 11. The frequency of late diagnosis of lung cancer also varies among histological types 10, 11…”
Section: Introductionmentioning
confidence: 99%
“…Lung cancer is the leading cause of cancer-related death worldwide in both men and women [1][2][3]. Non-small cell lung cancer (NSCLC) accounts for 80% of all lung cancer cases.…”
Section: Introductionmentioning
confidence: 99%